Comparison of Red Cell Distribution Width Values towardsMortality in Adult and Elderly Hospital-Acquired PneumoniaPatients in Dr. Sardjito Hospital - Sari, Desty Gusti; Asdie, Rizka Humardewayanti; Retnowulan, Heni (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. Hospital-acquired pneumonia (HAP) is a major cause of morbidity and mortality. Red cell distribution width (RDW) is associated with mortality in patients with septic shock and community-acquired pneumonia (CAP). However, little is known about the effect of elevation of RDW value on mortality in HAP patients, especially in the elderly population who have a worse prognosis. This study aimed to determine the proportion of adult and elderly HAP patients who have an increase in RDW value and the relation between the increase in RDW value to the risk of mortality in HAP patients during hospitalization. Methods. A cross-sectional and retrospective cohort study was performed using medical records of inpatients diagnosed with HAP in RSUP Dr. Sardjito Yogyakarta from March 2014 until March 2015. The study’s sample was chosen by a consecutive sampling method. The data were analyzed with chi-square and logistic regression. Results. During the study period, a total of 106 patients were diagnosed with HAP with fulfilled the inclusion and exclusion criteria. Sixty-eight subjects (64.15%) survived, and 38 subjects (35.84%) died. The median RDW value was 15.3% (range 11.4 – 29.8%). The proportion of adult and elderly HAP patients toward the increase in RDW value was not statistically significant (p=0.331). Factor contributing to the increase of RDW value was haemoglobin (p<0.001; RR 5.617 (95% CI 2.294 – 13.756) and thrombocyte (p=0.002; RR 4.471 (95% CI 1.720 – 11.625). There was a proportion difference between RDW value and HAP mortality (p=0.043), but it was not statistically significant. Factor contributing to the increase of HAP mortality was sepsis (p<0.001; RR 7.121 (95% CI 2.599-19.509)) and leucocyte (p=0.031; RR=3.077 (95% CI 1.108 – 8.546)). Conclusions. There is no proportion difference in increasing RDW value between adult and elderly HAP patients. We also found that RDW value was not contributing to make the increase in mortality among HAP patients. However, this study found other factors, including haemoglobin and platelet level which correlated with the increase of RDW. We also found that sepsis and high leukocyte levels are significantly correlated with the incidence of mortality among HAP patients.